Alpha-Enolase Protects Hepatocyte Against Heat Stress Through Focal Adhesion Kinase-Mediated Phosphatidylinositol 3-Kinase/Akt Pathway - Zeng, Tao; Cao, Yongqing; Gu, Tiantian; Chen, Li; Tian, Yong; Li, Guoqin; Shen, Junda; Tao, Zhenrong; Lu, Lizhi (Frontiers in Genetics, 2021)
Accumulating evidences showed that α-enolase (ENO1) is a multifunctional protein that plays a crucial role in a variety of pathophysiological processes. In our previous study, differential expression of ENO1 were observed in different heat-tolerance duck breeds. Here, we examined in vitro expression level of ENO1 in hepatocytes against heat stress. The mechanisms of ENO1 on cell glycolysis, growth and its potential regulatory pathways were also analyzed. The results showed that ENO1 expression in mRNA and protein levels were both greatly increased in heat-treated cells compared to non-treated cells. ENO1-overexpressed significantly elevated cell viability and glycolysis levels. It was further shown that stably upregulated ENO1 activated FAK-PI3K/AKT and its downstream signals. In addition, the interaction between ENO1 and HSP70 was detected using co-immunoprecipitation (co-IP). Our research suggests that ENO1 may interact with HSP70 to protect hepatocyte against heat stress through FAK-mediated PI3K/AKT pathway.